1996
DOI: 10.1620/tjem.179.81
|View full text |Cite
|
Sign up to set email alerts
|

Lung Microvascular Pressure Profile in Acute Lung Injury.

Abstract: To clarify the role of microvessels in the development of pulmonary hypertension of acute lung injury, we induced lung edema by oleic acid (OA) in ten artificially perfused cat lungs and measured microvascular pressure. Pulmonary artery pressure (Ppa) and pressure of 30-50 microns arteriole (Parteriole) increased from 19.2 +/- 1.4 and 15.7 +/- 1.0 cmH2O before to 30.5 +/- 5.0 cmH2O and 22.7 +/- 2.4 cmH2O after edema, respectively. Pressure of 30-50 microns venule (Pvenule) and venous occlusion pressure (Pvo) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…There are numerous experimental studies in which cats are used as a model for PH. In one study designed to assess the role of microvascular pressure in the development of PH, 68 oleic acid was used to induce acute lung injury in artificially perfused feline lungs. The authors demonstrated that in this model of acute lung injury an increase in microvascular resistance was followed by an increase in the arterial resistance and PAH.…”
Section: Classification Of Phmentioning
confidence: 99%
“…There are numerous experimental studies in which cats are used as a model for PH. In one study designed to assess the role of microvascular pressure in the development of PH, 68 oleic acid was used to induce acute lung injury in artificially perfused feline lungs. The authors demonstrated that in this model of acute lung injury an increase in microvascular resistance was followed by an increase in the arterial resistance and PAH.…”
Section: Classification Of Phmentioning
confidence: 99%